2019
DOI: 10.1111/modl.12589
|View full text |Cite
|
Sign up to set email alerts
|

The Social Lives of Adolescent Study Abroad Learners and Their L2 Development

Abstract: This article reports a longitudinal case study of two German high‐school exchange students’ 5.5‐month study abroad (SA) in New Zealand, examining their social lives and oral second language (L2) development. Six informal interviews, weekly diary entries, and monthly summaries were used to elicit data about their overseas experiences and reflections associated with them. The qualitative analysis investigated the nature of the students’ social lives at school, in their homestay, in their hobbies, and during thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Additional studies, such as Shiri (2015) on L2 Arabic and Sauer and Ellis (2019) on L2 English have used questionnaires, diary entries, and participant interviews to gather primarily qualitative data about learner socialization, social networks, and integration into the TL community during SA. This research demonstrates a correlation between social networks and global oral proficiency gains during SA (Shiri, 2015) and highlights the impact of social networks on the L2 development of grammatical complexity and accuracy, lexical diversity, and fluency (CALF; Sauer & Ellis, 2019). These studies are further supported by complementary research that provides detailed examinations of learner-TL speaker L2 Journal Vol.…”
Section: Opportunities For Interactions With Tl Speakersmentioning
confidence: 56%
“…Additional studies, such as Shiri (2015) on L2 Arabic and Sauer and Ellis (2019) on L2 English have used questionnaires, diary entries, and participant interviews to gather primarily qualitative data about learner socialization, social networks, and integration into the TL community during SA. This research demonstrates a correlation between social networks and global oral proficiency gains during SA (Shiri, 2015) and highlights the impact of social networks on the L2 development of grammatical complexity and accuracy, lexical diversity, and fluency (CALF; Sauer & Ellis, 2019). These studies are further supported by complementary research that provides detailed examinations of learner-TL speaker L2 Journal Vol.…”
Section: Opportunities For Interactions With Tl Speakersmentioning
confidence: 56%
“…Similarly, an interview study by Ehrenreich (2008) among 22 former German language assistants who taught German in English-speaking countries revealed that, for more than half of the assistants, interactions with the local population were rare. These findings can be partially accounted for by contextual constraints, such as students' accommodation or type of university program (Bracke & Aguerre, 2015;Mitchell, 2015), the sociolinguistic context (e.g., the presence of many other students from one's own country or with similar linguistic backgrounds; Mas-Alcolea & Torres-Purroy, 2022), or the availability of opportunities to invest in a hobby, such as in a local sports club (Sauer & Ellis, 2019). Individual factors can also contribute to this phenomenon.…”
Section: Social Network During Samentioning
confidence: 99%
“…As shown in a study by Sauer and Ellis (2019), two German‐speaking students learning English in New Zealand assumed different identities in homestay, the SA program, and outside school. Accordingly, their social affordances and learning opportunities were differentially presented in different contexts, leading to distinctive learning trajectories.…”
Section: Transdisciplinary Framework and Sa Researchmentioning
confidence: 99%